Optimalisasi Akurasi Baca Meter dengan implementasi Peta RBM (Rute Baca Meter) Berbasis App Mobile di ULP Belanti - Fadil Muhammad; Hansi Effendi (Jurnal Teknik Elektro Indonesia, 2021)
The PLN Company already has an application called ACMT or more precisely the Centralized Meter Record Application. This application also has the advantage that customers can access their meter data online. However, this application is not fully effective because not all customers have Android or if they already have Android but do not have an internet package because of the difficulty of finding input during this pandemic. Therefore, the appsheet describes the solution to this problem, namely the appsheet application can only be accessed by PLN officers who are carrying out their duties and the data is always updated. The use of this appsheet can make it easier for customers and can also help officers make their job easier